2012
DOI: 10.1016/j.intell.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention to emotional stimuli: What IQ and openness do, and emotional intelligence does not

Abstract: We examined how general intelligence, personality, and emotional intelligence-measured as an ability using the MSCEIT-predicted performance on a selective-attention task requiring participants to ignore distracting emotion information. We used a visual prime in which participants saw a pair of faces depicting emotions; their task was to focus on one of the faces (the target) while ignoring the other (the distractor). Next, participants categorized a string of letters (word or nonword), which was either congrue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 70 publications
3
36
1
2
Order By: Relevance
“…Moreover, given the distinction intelligence theorists have made between fluid (Gf) and crystallized intelligence (Gc), fruitful findings may also emerge from future research examining the relationship between EI and Gf versus Gc. Previous findings have suggested a relationship between the MSCEIT and both Gf (e.g., Di Fabio & Palazzeschi, 2009;Fiori & Antonakis, 2012) and Gc (Mayer, Roberts, et al, 2008). As well, within our own dataset, we found significant correlations between the MSCEIT and variables arguably tapping Gf (MSCEIT-WASI [Performance IQ] r =.43) and Gc (MSCEIT-WASI [vocabulary subtest] r = .542).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, given the distinction intelligence theorists have made between fluid (Gf) and crystallized intelligence (Gc), fruitful findings may also emerge from future research examining the relationship between EI and Gf versus Gc. Previous findings have suggested a relationship between the MSCEIT and both Gf (e.g., Di Fabio & Palazzeschi, 2009;Fiori & Antonakis, 2012) and Gc (Mayer, Roberts, et al, 2008). As well, within our own dataset, we found significant correlations between the MSCEIT and variables arguably tapping Gf (MSCEIT-WASI [Performance IQ] r =.43) and Gc (MSCEIT-WASI [vocabulary subtest] r = .542).…”
Section: Discussionsupporting
confidence: 87%
“…This implies that, instead of attempting to measure it as either of the two, it would be more valid to use both ability and trait measures or alternatively develop an independent measure that does not lie within the two restrictions. This viewpoint is backed by Fiori and Antonakis (2012), who conclude that what poses concern when the construct is measured as either a trait or ability is that there is much overlap with existing personality traits, to the extent of becoming redundant. It is imperative to consider the approach that looks at emotional intelligence as an ability as more theoretically apt when compared to the trait approach (Boyle et al, 2015;Fiori & Antonakis, 2012).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…This viewpoint is backed by Fiori and Antonakis (2012), who conclude that what poses concern when the construct is measured as either a trait or ability is that there is much overlap with existing personality traits, to the extent of becoming redundant. It is imperative to consider the approach that looks at emotional intelligence as an ability as more theoretically apt when compared to the trait approach (Boyle et al, 2015;Fiori & Antonakis, 2012). Nonetheless, Walter et al (2012) proposed that emotional intelligence should not replace already known predictors of leadership and performance; rather, it should complement them and as such deserves consideration.…”
Section: Emotional Intelligencementioning
confidence: 99%
“…The scientific investigation of the relationship between general intelligence and social-emotional abilities can be dated back to Terman [2], and Spearman's psychometric theory of intelligence believes that there are at least modest correlations between general intelligence and an individual's social-emotional abilities [3]. Many empirical studies also indicate that general intelligence quotient (IQ) is associated with social-emotional abilities [4][5][6][7][8]. Fiori and Antonakis [4] found that general intelligence could predict participant's faster responses during selective attention on emotional stimuli, which suggests that general intelligence is essential for performance involving emotional activation.…”
Section: Introductionmentioning
confidence: 99%
“…Many empirical studies also indicate that general intelligence quotient (IQ) is associated with social-emotional abilities [4][5][6][7][8]. Fiori and Antonakis [4] found that general intelligence could predict participant's faster responses during selective attention on emotional stimuli, which suggests that general intelligence is essential for performance involving emotional activation. Zeidner et al [8] observed that academically gifted adolescents had better emotional abilities relative to non-gifted adolescents.…”
Section: Introductionmentioning
confidence: 99%